(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2018)
The current study includes 144 samples were 106 bacterial samples belonging to the clinical sources, 38 bacterial samples belonging to the environmental sources to investigate the presence of bacteria P. aeruginosa. The results of diagnosis clarified that there are 45 bacterial isolates belonging to the bacterium P. aeruginosa The examination of the sensitivity of all bacterial isolates was done for elected 45 isolation towards the 11 antibiotic by spread method on the dishes. The results showed that the resistance ratio toward Cefixim, Cefotaxim, Tetracycline, Amoxicillin, Cloxacillin, Methicillin, Erythromycin and Naldixic acid was 77.7, 73.3, 84.4, 82.2, 80, 77.7, 77.7 and 73.3 respectively, While most isolates were sensitive to all of the antibiotic, Meropenem as did the proportion of resistance to this antibiotic 13.3%. Minimum inhibitory concentration (MIC) of the alcohol extract of Thymus vulgaris was determined. Results obtained showed that MIC of Thymus vulgaris extract was 15 mg/ ml. The antimicrobial activity of the alcohol extract of Thymus vulgaris was investigated for the purpose of inactivation of growth and production of virulence factors of P. aeruginosa that was isolated from clinical and environmental sources. The Results showed that alcohol extract of Thymus vulgaris had an inhibitory effect against P. aeruginosa The study was also carried out to study the synergism effect of antibiotics in presence of active compounds of the alcohol extract of Thymus vulgaris, where eight types of antibiotics were chosen that have resistance by P. aeruginosa and determined activity in presence of alcohol extract of Thymus vulgaris in concentration (15 mg /ml) that given Minimum inhibitory concentration (MIC) against P. aeruginosa, These antibiotics were Cefixim, Cefotaxim, Tetracycline, Amoxicillin, Erythromycin, Methicillin, Cloxacillin, and Naldixic acid. The Results showed that P. aeruginosa increased sensitivity to these antibiotics used in presence of active compounds of the alcohol extract of Thymus vulgaris.